DAYA HASIL BEBERAPA KULTIVAR SORGUM (Sorghum bicolor L.) PADA JARAK TANAM YANG BERBEDA - Mukhibbatul ' Khasanah; Aslim ' Rasyad; Elza ' Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this research was to determine the yield of four sorghum cultivars at different plant spacing and find out proper plant spacing for each sorghum cultivars. This research was conducted in the Agriculture experiment statiou and in plant breeding laboratory, Riau University from April 2015 to Agustus 2015. The parameters those observed were plant height, number of stem internodes, stem diameter, panicle length, time to harvest, grain weight per panicle, number of grains per panicle, yield per m2 and weight of 1000 grains. The results showed that increasing plant population per area due tothick planting space increasedgrain yield for 27% to 36.33% compare to wider planting space. Patir 9 as a new line developed by BATAN with 75 cm between row and 15 cm within a row has the high yield potential compared with other cultivars. Keywords: sorghum cultivars, plant spacing, yield